Enhancing Metal–Support Interactions by Molybdenum Carbide: An Efficient Strategy toward the Chemoselective Hydrogenation of α, β‐Unsaturated Aldehydes. Issue 16 (2nd March 2016) - He, Sina; Shao, Zheng‐Jiang; Shu, Yijin; Shi, Zhangping; Cao, Xiao‐Ming; Gao, Qingsheng; Hu, Peijun; Tang, Yi
Abstract: Metal–support interactions are desired to optimize the catalytic turnover on metals. Herein, the enhanced interactions by using a Mo2 C nanowires support were utilized to modify the charge density of an Ir surface, accomplishing the selective hydrogenation of α, β‐unsaturated aldehydes on negatively charged Ir δ− species. The combined experimental and theoretical investigations showed that the Ir δ− species derive from the higher work function of Ir (vs. Mo2 C) and the consequently electron transfer. In crotonaldehyde hydrogenation, Ir/Mo2 C delivered a crotyl alcohol selectivity as high as 80 %, outperforming those of counterparts (<30 %) on silica. Moreover, such electronic metal–support interactions were also confirmed for Pt and Au, as compared with which, Ir/Mo2 C was highlighted by its higher selectivity as well as the better activity. Additionally, the efficacy for various substrates further verified our Ir/Mo2 C system to be competitive for chemoselective hydrogenation. Abstract : Enhanced interactions by Mo2 C nanowires are introduced to effectively optimize the charge density of Ir, as validated by combined experimental and theoretical investigations. The Ir δ − species on Mo2 C favors the selective hydrogenation of α, β‐unsaturated aldehydes to the corresponding unsaturated alcohols (see figure; MSI=metal–support interactions).